Properties of composite cement-sodium silicate grout mixed with sulphoaluminate cement and slag powder in flowing water. (15th November 2021) - Lin, Rongfeng; Yang, Lei; Pan, Guangming; Sun, Zizheng; Li, Jinglong
Highlights: The composite cement-sodium silicate grout mixed with SC and SLP are prepared. Properties of composite grout in the still and flowing water are examined. Scouring effect of flowing water causes negative effects on the grout concretion. Appropriate dosages of SC and SLP improve the anti-scour ability of grout concretion. Abstract: The properties of grouting materials within the flowing-water environment impact greatly the long-term effect of water-plugging engineering. In order to improve the performance of traditional cement-sodium silicate grouting material, the composite cement-sodium silicate grout mixed with sulphoaluminate cement and slag powder was prepared, and the properties of the composite grout and its concretion within the still and flowing water environments are investigated experimentally. The test results indicate that the scouring effect of flowing water causes negative effects on the strength and anti-permeability of grout concretion. Oppositely, the substitution of two admixtures with proper ratios improves obviously the comprehensive performances of composite grout to resist the effect of flowing water.